Development of picosecond time‐resolved X‐ray absorption spectroscopy by high‐repetition‐rate laser pump/X‐ray probe at Beijing Synchrotron Radiation Facility. (24th March 2017) - Wang, Hao; Yu, Can; Wei, Xu; Gao, Zhenhua; Xu, Guang-Lei; Sun, Da-Rui; Li, Zhenjie; Zhou, Yangfan; Li, Qiu-Ju; Zhang, Bing-Bing; Xu, Jin-Qiang; Wang, Lin; et al.
Abstract : The detection of transient X‐ray absorption spectroscopy has been realised using a high‐repetition‐rate laser pump/X‐ray probe method at a wiggler beamline. A picosecond X‐ray absorption near‐edge spectrum was obtained for a photo‐induced spin‐crossover iron complex. Abstract : A new setup and commissioning of transient X‐ray absorption spectroscopy are described, based on the high‐repetition‐rate laser pump/X‐ray probe method, at the 1W2B wiggler beamline at the Beijing Synchrotron Radiation Facility. A high‐repetition‐rate and high‐power laser is incorporated into the setup with in‐house‐built avalanche photodiodes as detectors. A simple acquisition scheme was applied to obtain laser‐on and laser‐off signals simultaneously. The capability of picosecond transient X‐ray absorption spectroscopy measurement was demonstrated for a photo‐induced spin‐crossover iron complex in 6 m M solution with 155 kHz repetition rate.